SECURITISATION OF CLIMATE CHANGE: THE RISK OF EXAGGERATION - JEROEN WARNER; INGRID BOAS (Ambiente & Sociedade, 2017)
Abstract The present contribution focuses on the ‘selling’ of the ‘climate crisis’ to intended key audiences, both in the international domain and at home. We look into the mechanics of crisis framing, the audience, and the resonance that the frame had, as well as development over time in two cases: the UK addressing the UN Security Council and the State Advisory Commission on Deltas (‘Delta Commission’) seeking support in the Netherlands for drastic measures to address sea level rise. For this, we apply the conceptual framework from critical security studies and securitisation, with contributions from the domains of crisis and disaster studies. Both case studies discussed show a dramatic securitising move, where climate change is presented as the source of great potential crisis that will harm us all, unless we take urgent action - either for mitigation (the reduction of greenhouse gas emissions) or for adaptation.